2014
DOI: 10.1103/physrevd.90.124084
|View full text |Cite
|
Sign up to set email alerts
|

Formation and decay of Einstein-Yang-Mills black holes

Abstract: We study various aspects of black holes and gravitational collapse in Einstein-Yang-Mills theory under the assumption of spherical symmetry. Numerical evolution on hyperboloidal surfaces extending to future null infinity is used. We begin by constructing colored and Reissner-Nordström black holes on surfaces of constant mean curvature and analyze their perturbations. These linearly perturbed black holes are then evolved into the nonlinear regime and the masses of the final Schwarzschild black holes are compute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…However, both the solitons and hairy black holes were soon found to be unstable [11][12][13][14][15][16][17]. Under perturbation, the black holes lose their gauge-field hair and evolve towards a (stable) vacuum black hole solution; the solitons either collapse to form a vacuum black hole or else the gauge field is radiated away to infinity, leaving pure Minkowski spacetime [18][19][20]. This prompts an intriguing question: are there scenarios in which the converse occurs, i.e., in which a vacuum black hole spontaneously evolves towards a hairy configuration which is stable?…”
Section: Introductionmentioning
confidence: 99%
“…However, both the solitons and hairy black holes were soon found to be unstable [11][12][13][14][15][16][17]. Under perturbation, the black holes lose their gauge-field hair and evolve towards a (stable) vacuum black hole solution; the solitons either collapse to form a vacuum black hole or else the gauge field is radiated away to infinity, leaving pure Minkowski spacetime [18][19][20]. This prompts an intriguing question: are there scenarios in which the converse occurs, i.e., in which a vacuum black hole spontaneously evolves towards a hairy configuration which is stable?…”
Section: Introductionmentioning
confidence: 99%
“…2 In particular, this interesting numerical study [13] has explicitly demonstrated that, during a near-critical evolution of the Yang-Mills field, the time spent in the vicinity of an unstable SU(2) Reissner-Nordström black-hole solution is characterized by the critical scaling law 3…”
Section: Introductionmentioning
confidence: 99%
“…The recent numerical work of Rinne [13] has revealed that these unstable SU(2) Reissner-Nordström black-hole spacea e-mail: shaharhod@gmail.com times play the role of approximate 1 codimension-two intermediate attractors (that is, nonlinear critical solutions [14]) in the dynamical gravitational collapse of the Yang-Mills field. 2 In particular, this interesting numerical study [13] has explicitly demonstrated that, during a near-critical evolution of the Yang-Mills field, the time spent in the vicinity of an unstable SU(2) Reissner-Nordström black-hole solution is characterized by the critical scaling law 3…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations